2018
DOI: 10.3389/fpsyt.2018.00677
|View full text |Cite
|
Sign up to set email alerts
|

A Conscious Resting State fMRI Study in SLE Patients Without Major Neuropsychiatric Manifestations

Abstract: Neuropsychiatric systemic lupus erythematosus (NPSLE) is one of the main causes of death in patients with systemic lupus erythematosus (SLE). Signs and symptoms of NPSLE are heterogeneous, and it is hard to diagnose, and treat NPSLE patients in the early stage. We conducted this study to explore the possible brain activity changes using resting state functional magnetic resonance imaging (rs-fMRI) in SLE patients without major neuropsychiatric manifestations (non-NPSLE patients). We also tried to investigate t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(36 reference statements)
0
21
0
Order By: Relevance
“…Conventional MRI studies reveal decreased hippocampal volumes in SLE patients with CD compared to those without CD (10). One study demonstrated decreased activation of the hippocampus/parahippocampal gyrus on functional MRI during a spatial working memory task in SLE patients (11), and another study showed abnormal regional activity in the parahippocampal gyrus on functional MRI during the resting state (12). This is of interest, as multiple lines of evidence in rodent models indicate that hippocampal integrity is critical for spatial memory (13).…”
Section: Neuroimaging In Sle CDmentioning
confidence: 99%
“…Conventional MRI studies reveal decreased hippocampal volumes in SLE patients with CD compared to those without CD (10). One study demonstrated decreased activation of the hippocampus/parahippocampal gyrus on functional MRI during a spatial working memory task in SLE patients (11), and another study showed abnormal regional activity in the parahippocampal gyrus on functional MRI during the resting state (12). This is of interest, as multiple lines of evidence in rodent models indicate that hippocampal integrity is critical for spatial memory (13).…”
Section: Neuroimaging In Sle CDmentioning
confidence: 99%
“…Several previous studies reported that static ReHo was altered in non-NPSLE patients. 14 , 33 Specifically, active patients with SLE showed decreased ReHo in the right fusiform gyrus and increased ReHo in the left parahippocampal and right uncus. 14 , 33 However, static ReHo can only reflect static local brain activity.…”
Section: Discussionmentioning
confidence: 96%
“…For example, researchers found increased standardized ALFF in the left inferior temporal gyrus and left putamen in patients with non-NPSLE and the significantly negative correlation between C3 and ALFF values in the left putamen was found in patients. 13 Liu et al 14 found abnormal ReHo in the parahippocampal gyrus, fusiform gyrus, and thalamus in non-NPSLE patients and ReHo values in the left postcentral gyrus were negatively correlated with anxiety depression symptoms. Yu et al 15 found decreased ALFF in the precuneus and increased ALFF in the right cuneus and right calcarine fissure surrounding cortex in non-NPSLE patients.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The advantage of fMRI is its ability to detect variations in the deoxyhemoglobin levels in neurons as a measure of neuronal activity, serving as an indirect assessment of cerebral functions such as working memory, executive function, and attention 34 . Different studies demonstrated abnormalities in the hippocampal/parahippocampal regions of patients with SLE both at rest and during a memory task 35,36 .…”
Section: Neuroimagingmentioning
confidence: 99%